2013
DOI: 10.3141/2397-09
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Travel Behavior and Transit Trip Generation Characteristics of Transit-Oriented Developments

Abstract: Transit-oriented developments (TODs) have been recognized as a promising proposition for policy makers and land developers in meeting the challenges of urban sprawl. The rapid pace with which TODs are being developed across the United States has left policy makers and transportation planners looking for methods aimed at modeling the travel characteristics of TODs. Current ITE trip-generation models are generally based on consolidated survey data from various land uses and are inadequate for serving the plannin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 6 publications
0
20
0
Order By: Relevance
“…Faghri and Venigalla (2013) found that most households own at least one car in TODs in Washington, D.C. Nevertheless, the overall level of vehicle ownership was much lower in TOD areas and despite owning a car, the rate of car use in TODs was lower than in non-TOD areas.…”
Section: Travel Behaviour In Transit Oriented Developmentmentioning
confidence: 85%
See 1 more Smart Citation
“…Faghri and Venigalla (2013) found that most households own at least one car in TODs in Washington, D.C. Nevertheless, the overall level of vehicle ownership was much lower in TOD areas and despite owning a car, the rate of car use in TODs was lower than in non-TOD areas.…”
Section: Travel Behaviour In Transit Oriented Developmentmentioning
confidence: 85%
“… Third, car use might be necessary for some of them due to a lack of PT service coverage to their destinations as found in other TOD context (Faghri and Venigalla, 2013). Further research showing the activity spaces of these groups and comparing with an existing PT service coverage map would enable to identify the coverage gaps, and subsequent provisioning.…”
Section: Discussionmentioning
confidence: 97%
“…The ITE Parking Generation manual notes that study sites upon which the manual is based are "primarily isolated, suburban sites" (ITE 2010). Studies show that the vehicle ownership is lower in transit-served areas than those that are not transit-served (Faghri and Venigalla 2013;Zamir et al 2014). By comparing parking-generation rates for housing projects near rail stops with parking supplies and with ITE's parking-generation rates, Cervero et al (2010) found there is an oversupply of parking near transit, sometimes by as much as 25-30 percent.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Another study by the San Francisco Bay Area Metropolitan Transportation Commission found that residents living near transit generated half as many vehicle miles traveled (VMT) as their suburban and rural counterparts (SFBAMTC 2006). At the same time, Bay Area residents living in developments near transit are reported to have higher rates of transit trips than living at greater distances (Faghri and Venigalla 2013;SFBAMTC 2006;Zamir et al 2014), especially for commuting trips Cervero 1994;Faghri and Venigalla 2013;Lund et al 2004;Lund et al 2006). …”
Section: Literature Reviewmentioning
confidence: 99%
“…TOD impacts are measured by studying mode choice variations before and after relocating to a TOD environment and also by comparing mode choice in TOD environments with non-TOD environments. Results of an analysis of data associated with the greater Washington DC area show that work, shop, and entertainment trips in TOD areas were performed mainly via transit (Faghri and Venigalla 2013;Faghri 2012). Messenger and Ewing (1996) observed that bus mode share by place of residence proved to be dependent primarily on automobile ownership and secondarily on jobs-housing balance and bus service frequency.…”
Section: Introductionmentioning
confidence: 99%